A PRAGMATIC ANALYSIS OF THE AFFECTION EXPRESSION IN TWILIGHT AND TWILIGHT: NEW MOON MOVIES - QOMARUDINALI , UMAR (2010)
This research deals with the affection expression in the Twilight and Twilight: new moon movies. The aims of this research are to describe the types of speech act of affection expression, to describe the intention of affection expression and to describe the function of affection expression in Twilight and Twilight: new moon movies. The writer employs the descriptive qualitative as the type of the research. The data source of this research is Twilight and Twilight: new moon movies. The technique of analyzing data of this research are to describe the types of speech of affection, the writer refers to classification of speech act by Searle classification, to describe the intentions, the writer uses the speech act theory by Austin, to describe functions, the writer uses speaking formula by Hymes, and drawing the conclusion and suggestions based on the data analysis. From the data analysis the writer finds there are four types of speech act, namely: 14.81% belongs to directive utterance, 33.33% belongs to commisive utterance, 48.13% belongs to expressive utterance, and 3.07% belongs to declarative utterance. The intentions of affection expression, namely: 14.81% belongs to requesting utterance, 22.22% belongs to promising utterance, 11.11% belongs to vowing utterance, 14.81% belongs to congratulating utterance, 3.70% belong to praising utterance, 29.62% belongs to stating utterance, and 3.70% belongs to naming utterance. The functions of affection expression namely: 14.81% belongs to requesting utterance, 22.22% belongs to promising utterance, 11.11% belongs to vowing utterance, 14.81% belongs to congratulating utterance, 3.70% belong to praising utterance, 29.62% belongs to stating utterance, and 3.70% belongs to naming utterance.